2011
DOI: 10.1002/app.33528
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic natural rubber based on polyamide‐12: Influence of blending technique and type of rubber on temperature scanning stress relaxation and other related properties

Abstract: Thermoplastic natural rubber based on polyamide-12 (PA-12) blend was prepared by melt blending technique. Influence of blending techniques (i.e., simple blend and dynamic vulcanization) and types of natural rubber (i.e., unmodified natural rubber (NR) and epoxidized natural rubber (ENR)) on properties of the blends were investigated. It was found that the simple blends with the proportion of rubber $ 60 wt % exhibited cocontinuous phase structure while the dynamically cured blends showed dispersed morphology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…The mechanical, thermal and chemical properties of a TPV are dependent on the morphology developed during melt processing [1]. TPVs are produced by a dynamic process of vulcanization/crosslinking achieved through specific chemical reactions in the elastomeric phase using a crosslinking agent, resulting in the formation of new covalent bonds and an increase in the molecular weight and viscosity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical, thermal and chemical properties of a TPV are dependent on the morphology developed during melt processing [1]. TPVs are produced by a dynamic process of vulcanization/crosslinking achieved through specific chemical reactions in the elastomeric phase using a crosslinking agent, resulting in the formation of new covalent bonds and an increase in the molecular weight and viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…TPVs are produced by a dynamic process of vulcanization/crosslinking achieved through specific chemical reactions in the elastomeric phase using a crosslinking agent, resulting in the formation of new covalent bonds and an increase in the molecular weight and viscosity. The elastomeric phase in TPVs is fragmented by the action of mechanical forces during melt processing and dispersed in the thermoplastic phase (1-5 µm in diameter) [1]- [3]. The combination of behaviors similar to those of rubber and thermoplastic melts results in polymer system with a two-phase morphology: the soft phase, an elastomer, gives the rubber-like properties in the solid state, whereas the hard phase shows the properties of a thermoplastic polymer with a high glass transition temperature, which gives strength to the blend [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms combination effects of dynamic vulcanization and chemical interaction between ENR and PA-12 molecules that enhance the stress relaxation properties. 19,24 Therefore, it is concluded that the dynamically cured ENR/PA-12 blends gave higher area underneath the normalized force-temperature curves than those of the ADS/PA-12 blends. Table 6 summarizes the TSSR results based on Figures 6 and 7.…”
Section: Rheological Propertiesmentioning
confidence: 95%
“…The slope of the increasing stress corresponded to the crosslinking density6 and/or the interaction between both phases8 in those materials. For TPV, the entropic effect, therefore, is an important phenomenon related to the interactions of the blend components.…”
Section: Methodsmentioning
confidence: 99%